2018
DOI: 10.1186/s12873-018-0161-x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety about anxiety: a survey of emergency department provider beliefs and practices regarding anxiety-associated low risk chest pain

Abstract: BackgroundApproximately 80% of patients presenting to emergency departments (ED) with chest pain do not have any true cardiopulmonary emergency such as acute coronary syndrome (ACS). However, psychological contributors such as anxiety are thought to be present in up to 58%, but often remain undiagnosed leading to chronic chest pain and ED recidivism.MethodsTo evaluate ED provider beliefs and their usual practices regarding the approach and disposition of patients with low risk chest pain associated with anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Based on prior work we estimated that approximately 30% of low risk chest pain patients would score ≥8 on the HADS-A, indicating abnormal anxiety. 17 Thus, with a 95% confidence level and a 15% confidence interval width, the required sample size was estimated to be 154.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Based on prior work we estimated that approximately 30% of low risk chest pain patients would score ≥8 on the HADS-A, indicating abnormal anxiety. 17 Thus, with a 95% confidence level and a 15% confidence interval width, the required sample size was estimated to be 154.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A study conducted in China revealed that people were psychologically affected by the outbreak at moderate to severe levels during the pandemic (Wang, et al, 2020). It is also understood that a large number of patients with anxiety suffering from emergency immediate symptoms, admit to emergency departments (Musey, et al, 2018). As suggested by the present study, 52.8% of all the patients admitted to out emergency service were green room patients, who did not have an emergency symptom.…”
Section: Resultsmentioning
confidence: 49%
“…[5] Regarding the provider perception and response to patient anxiety, a national survey of 409 emergency physicians found that respondents believe that 30% of low risk chest pain had severe anxiety, but only 41% offer anxiety treatment. [6] Reasons for not treating anxiety may include the desire to avoid the side effects of anxiolytics, such as sedation, which can preclude driving home. Also, physicians are wary of generating a perception of labelling the patient as anxious, and implicitly discounting his or her reason for seeking emergency care.…”
Section: Introductionmentioning
confidence: 99%